Long-term follow-up of an IgA nephropathy cohort: outcomes and risk factors - Liliana Gadola; María Jimena Cabrera; Mariela Garau; Ruben Coitiño; María Haydée Aunchayna; Oscar Noboa; María Asunción Alvarez; Sylvia Balardini; Graciela Desiderio; Nelson Dibello; Alejandro Ferreiro; Soledad Giró; et al. (Renal Failure)
Aim IgA nephropathy (IgAN), the most common glomerulopathy worldwide and in Uruguay, raised treatment controversies. The study aimed to analyze long-term IgAN outcomes and treatment.Methods A retrospective analysis of a Uruguayan IgAN cohort, enrolled between 1985 and 2009 and followed up until 2020, was performed. The Ethics Committee approved the study. The inclusion criteria were (a) biopsy-proven IgAN; (b) age ≥12 years; and (c) available clinical, histologic, and treatment data. The patients were divided into two groups, with immunosuppressive (IS) or without (NoIS) treatment. Outcomes (end-stage kidney disease/kidney replacement therapy [ESKD/KRT] or all-cause death) were obtained from mandatory national registries.Results The study population included 241 patients (64.7% men), median age 32 (19.5) years, baseline blood pressure <130/80 mmHg in 37%, and microhematuria in 67.5% of patients. Baseline proteinuria, glomerulosclerosis, and a higher crescent percentage were significantly more frequent in the IS group. Proteinuria improved in both groups. Renal survival at 20 years was 74.6% without difference between groups. In the overall population and in the NoIS group, bivariate Cox regression analysis showed that baseline proteinuria, endocapillary hypercellularity, tubule interstitial damage, and crescents were associated with a higher risk of ESKD/KRT or death, but in the IS group, proteinuria and endocapillary hypercellularity were not. In the multivariate Cox analysis, proteinuria in the NoIS group, crescents in the IS group and tubule interstitial damage in both groups were independent risk factors.Conclusion The IS group had more severe risk factors than the NoIS group but attained a similar outcome.